Domains of decision-making and forms of capital among men and women teachers. Issue 6 (8th March 2020) - Grinshtain, Yael; Addi-Raccah, Audrey
Abstract : Purpose: Viewing school as a feminine bias workplace alongside being a field of power relations as argued by Bourdieu, this study examines (1) gender differences among teachers in different forms of capital (cultural, social, and feminine) and in their participation in decision-making (PDM) at school in three domains: managerial, administration, and teaching; (2) the relations between forms of capital and domains of PDM within each gender group. Design/methodology/approach: The study was based on a random sample of 32 schools in Northern Israel that included 595 teachers (454 women; 141 men) who answered a questionnaire, which included background information; teachers' forms of capital; and PDM in managerial, administrative, and teaching domains. Multiple regression analysis was conducted. Findings: Men tend to have an advantage in PDM in managerial issues, while women have an advantage in PDM in teaching. Further, women more than men perceived feminine capital and social capital as contributing to their work. It was also found that more types of capital are related to PDM among women as compared to men. For men, academic cultural capital predicts PDM in the teaching domain. For women, social capital predicts PDM in the three domains; academic cultural capital predicts PDM in the managerial domain; and feminine capital predicts PDM in teaching. Originality/value: This study focuses simultaneously on different forms of capital, emphasizing the varying contribution of each capital to men and to women teachers. It also offers a set of resources that can demonstrate the complex factors that contribute to teachers' work.